A predictive model for the effects of compression of fouling layers on the filtration performance of flat-sheet membrane bioreactors - Suzanne A. Yala; V.L. Pillay (Desalination and Water Treatment)
Compression of fouling layers has a major impact on the performance of a membrane bioreactor (MBR). In this study, a new model that can predict permeate flux decline (in constant pressure operations) or increase in transmembrane pressure (in constant flux operations) in an MBR, based on the filtration and compressibility characteristics of a feed, was developed. Experimental results from membrane filtration of 4 g/L of yeast suspension at both 40 kPa constant pressure and 35 LMH constant flux were used to estimate the model parameters. The model was then validated with data obtained from runs carried out at different applied pressure (10, 20, 50 and 60 kPa), different applied flux (15, 25, 45 and 55 LMH) and with different feed concentration (6 and 8 g/L). Across all the conditions, the model predictions were in good agreement with the experimental data. Additionally, the model was able to correctly forecast flux decline and pressure drop increase in the membrane filtration of real municipal wastewater under constant pressure and constant flux operations, respectively. It was also demonstrated that the model could also be used to gain mechanistic details on membrane fouling such as profiles of compressive pressure, porosity and specific cake resistance across fouling layers.